2017
DOI: 10.1080/02681102.2017.1311833
|View full text |Cite
|
Sign up to set email alerts
|

Technology-driven information sharing and conditional financial development in Africa

Abstract: Information technology is increasingly facilitating mechanisms by which information asymmetry between lenders and borrowers in the financial sector can be reduced in order to enhance financial access for human and economic development in developing countries. We examine sharing on financial depth (money supply and liquid liabilities) and financial activity (at banking and financial system levels). Second, for financial intermediation efficiency, the positive effects from mobile-driven information sharing are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 92 publications
(85 reference statements)
5
51
0
1
Order By: Relevance
“…Furthermore, human resources management can be problematic in operating these agent networks. Some studies indicate that firms and banks in developing countries find it difficult to recruit qualified employees and agents (Asongu, Anyanwu, & Tchamyou, ; Maurer et al, ; Potnis, ). Because most of them lack the necessary skills and the competence required for handling MFS delivery, they do not understand the operating process of the services and are unable to give appropriate information to their customers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, human resources management can be problematic in operating these agent networks. Some studies indicate that firms and banks in developing countries find it difficult to recruit qualified employees and agents (Asongu, Anyanwu, & Tchamyou, ; Maurer et al, ; Potnis, ). Because most of them lack the necessary skills and the competence required for handling MFS delivery, they do not understand the operating process of the services and are unable to give appropriate information to their customers.…”
Section: Resultsmentioning
confidence: 99%
“…These services have helped overcome infrastructural constraints and improve financial inclusion (Allen et al, ; Hinson, ; Maurer, ). Asongu et al () examined the use of mobile devices in African countries and showed that MFS have positive effects on financial depth and financial activity. Yet, there is only one article that empirically examines the effect of MFS on financial inclusion, which makes it difficult to firmly assert the effect of the services.…”
Section: Resultsmentioning
confidence: 99%
“…These services have helped overcome infrastructure constraints and improve inclusive finance (Allen et al, 2014;Hinson, 2011;Maurer, 2012). Asongu et al (2017) analyzed the use of mobile devices in African countries and showed that MFS has a positive impact on the financial development of these countries.…”
Section: Previous Studies On the Relationship Between Mobile Money Dmentioning
confidence: 99%
“…Triki and Gajigo () have established that, compared to PCRs, PCBs are associated with higher levels of financial access. Asongu, Nwachukwu, and Tchamyou () show that ISOs have influenced access to finance negatively and Asongu, Anyanwu, and Tchamyou () conclude that technology‐driven information sharing is relevant in driving financial access. Muazu and Alagidede () conclude that, compared to countries with French civil law traditions, their counterparts with English common law traditions benefit more from financial access arising from the introduction of ISOs.…”
Section: Introductionmentioning
confidence: 99%